Effect of Ozonized Solutions on Dynamics of Wound Process During Cold Damages of Rat’s Skin - Somova, E. V.; Kadnikova, N. G.; Tynynyka, L. N.; Zinchenko, V. D. (Problems of Cryobiology and Cryomedicine, 2006)
In the model of rat’s skin cold wounds microbe seeding has been studied, heat radiation on wound surface within infrared range has been measured and healing process at daily subcutaneous introduction of ozonized physiological solution (ozone concentration made 1.1 ml/l) into cold trauma site has been observed. It has been shown that wound treatment with ozonized physiological solution contributes to more intensive healing process of cold traumas, that manifests in reduction of total microbe seeding of animals skin and decrease in radiation values recorded within infrared range.